Anorexia e bulimia nervosa, perturbações alimentares para a vida? - Marta Daniela Pinto Dias (2020)
Introduction: Anorexia and bulimia nervosa are eating disorders with a high mortality rate among psychiatric diseases. These pathologies cause several medical complications in the short and long term. The aim of this study is to provide a better understanding of the medical complications that have long-term consequences for patients, even after the absence of clinical diagnostic criteria. Methods: A bibliographic search was performed in the Pubmed and Scopus search engines, with the following query: "Bulimia Nervosa" OR "Anorexia Nervosa" AND "Physical Consequences" The studies that linked anorexia and bulimia nervosa with their medical complications were included. Results: The medical impact of anorexia and bulimia nervosa is multiorganic. Several systems are affected in the acute and chronic phases of the disease. Studies show that most complications reverse with effective treatment. However, there are sequelae that remain even after the absence of clinical criteria for diagnosing pathologies. Discussion / Conclusion: It is important to know the impact of these eating behavior disorders in the body, in order to make possible a full and total recovery of patients, and not only the absence of clinical diagnostic criteria. Knowledge about the remaining limitations of these pathologies and the irreversible consequences on different organs is scarce. Further long-term follow-up studies of patients with these eating disorders are needed.